2012
DOI: 10.1152/jn.01108.2011
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of afferent neurons in larval zebrafish provides a functional framework for lateral line somatotopy

Abstract: Fishes rely on the neuromasts of their lateral line system to detect water flow during behaviors such as predator avoidance and prey localization. Although the pattern of neuromast development has been a topic of detailed research, we still do not understand the functional consequences of its organization. Previous work has demonstrated somatotopy in the posterior lateral line, whereby afferent neurons that contact more caudal neuromasts project more dorsally in the hindbrain than those that contact more rostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 50 publications
1
65
0
Order By: Relevance
“…In zebrafish, neural networks exhibit topographic patterns of functional organization due to their order of development (Kimura et al, 2006; McLean and Fetcho, 2009; Kinkhabwala et al, 2011; Koyama et al, 2011; Miri et al, 2011; Liao and Haehnel, 2012; Pujol-Marti et al, 2012; Satou et al, 2012). In the spinal cord, the networks that are recruited during the most powerful movements are the first to develop, with slower networks layered on as zebrafish grow into free-swimming larvae.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, neural networks exhibit topographic patterns of functional organization due to their order of development (Kimura et al, 2006; McLean and Fetcho, 2009; Kinkhabwala et al, 2011; Koyama et al, 2011; Miri et al, 2011; Liao and Haehnel, 2012; Pujol-Marti et al, 2012; Satou et al, 2012). In the spinal cord, the networks that are recruited during the most powerful movements are the first to develop, with slower networks layered on as zebrafish grow into free-swimming larvae.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that each neuron is pre-specified to occupy a particular position along the somatotopic axis. Importantly, cellular birth dating showed that neuronal morphology, behavior and projection pattern correlate with the time of neurogenesis (Liao, 2010; Pujol-Martí et al, 2010; Liao and Haehnel, 2012). During the first wave of neurogenesis, early differentiating lateralis afferents project dorsal central axons and innervate posterior neuromasts, whereas late-differentiating neurons project central axons more ventrally and innervate anterior neuromasts ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Very recent neuroanatomical work has re-explored the projection patterns of the lateralis afferent neurons in the zebrafish larva, putting emphasis on their connectivity (Faucherre et al, 2010; Liao, 2010; Haehnel et al, 2012; Liao and Haehnel, 2012; Pujol-Martí et al, 2012). These studies have revealed two classes of lateralis afferents in the posterior lateral line (Liao and Haehnel, 2012; Pujol-Martí et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals respond to touch as early as 21 hr postfertilization (hpf), indicating that coherent somatosensory circuits have formed 5,18 . During larval development at least some trigeminal and RB neurons synapse onto the Mauthner cell to activate classic escape responses, but accumulating evidence suggests that there are multiple classes of somatosensory neurons with different patterns of connectivity that may elicit variations on the escape behavior 2,4,10,12,14,15,16,17 . Our motivation for developing this method was to characterize the behavioral function of different classes of somatosensory neurons, but this approach could in principle be used to study the function of almost any neuron or population of neurons in larval zebrafish.…”
Section: Introductionmentioning
confidence: 99%